FACTORS THAT CONTRIBUTE TO THE DETERMINATION OF CLIMATIC INFLUENCES IN FORESTED AREAS - Cristina Carmen Stingu (Palici); Valentin Nedeff; Ion Sandu; Petronela Spiridon-Ursu; Mihaela Orlanda Antonovici (Munteanu) (Acta Geobalcanica, 2021)
The paper presents some aspects related to the role and functions protected areas, of the special avifaunistic protection area (SPA), included in the list of sites of community importance (SCI), belonging to the ecological network Natura 2000 in Iasi County, with the role and function of natural habitat conservation, of wild fauna and flora, from Barnova Forest (SPA0092) and Barnova Repedea Forest (ROSCI0135). A number of investigative methods and techniques were used to enhance protected areas that also integrate historical monuments, included in the list of sites of Community importance (SCI). Among the analyzed aspects, reference was made to monitoring the evolution of their conservation status, taking into account the new findings regarding instrumental analysis techniques as well as present methodological processing / operation systems, using the Geographic Information System (GIS), which will allow geographical representation and mapping of the characteristics contained in the relational databases. As a reference, the visual representation will be used, observing in the field the distribution of nature's goods and their affectation by climatic influences largely due to environmental aggression through anthropogenic actions, but also of historical monuments in the two study areas. The results of these analyzes will underline the overwhelming importance of maintaining a clean environment and sustainable growth will be pursued, providing biodiversity benefits. Stimulating beneficial actions will be achieved by maintaining and conserving the biodiversity of ecosystems and related services, reducing unsustainable practices.